Respuesta :
Let's simplify step-by-step.
0.2(3b−15c)+6c
Distribute:=(0.2)(3b)+(0.2)(−15c)+6c
=0.6b+−3c+6c
Combine Like Terms:
=0.6b+−3c+6c
=(0.6b)+(−3c+6c)
=0.6b+3c
0.2(3b−15c)+6c
Distribute:=(0.2)(3b)+(0.2)(−15c)+6c
=0.6b+−3c+6c
Combine Like Terms:
=0.6b+−3c+6c
=(0.6b)+(−3c+6c)
=0.6b+3c
To simplify, we apply distributive property
0.2*3b - 0.2*15c +6c
0.6b-3c+6c
Now we combine like terms.
-3c and 6c are like terms.
-3c+6c= 3c
Re-write our expression
0.6b+3c
FINAL ANSWER: 0.6b+3c
0.2*3b - 0.2*15c +6c
0.6b-3c+6c
Now we combine like terms.
-3c and 6c are like terms.
-3c+6c= 3c
Re-write our expression
0.6b+3c
FINAL ANSWER: 0.6b+3c